Questionnaire-based mechanical exposure indices for large population studies - reliability, internal consistency and predictive validity - Balogh, Istvan; Ørbaek, Palle; Winkel, Jörgen; Nordander, Catarina; Ohlsson, Kerstina; Ektor-Andersen, John; 10.5271/sjweh.585, Malmö Shoulder-Neck Study GroupM3 -. doi: (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'This study attempts to construct valid indices for mechanical exposure of the shoulder-neck region with relation to the development of shoulder-neck pain in a 1-year perspective study of a general population. ' ' METHODS ': 'A comprehensive questionnaire was presented to 14 556 subjects aged 45 or 65 years and repeated after 12 months. Twenty-four questions concerning positions, movements, and manual materials handling were registered on a 3-point impact scale. Musculoskeletal problems were reported on a slightly modified version of the Standardized Nordic Questionnaire for the Analysis of Musculoskeletal Symptoms. Test-retest stability after 2 weeks was calculated for 232 consecutive participants. Based on mechanistic theories, 4 exposure indices were formed. Another 5 constructs were obtained by factor analysis. ' ' RESULTS ': 'All the indices showed good test-retest stability, and 5 of them had very good internal consistency. Due to overlaps between the indices, 2 indices stood out as having unique properties. One of them concerned mainly postures and the other dealt primarily with measured lifting. However, the latter was not related to the shoulder-neck pain outcome when adjusted for the posture index. The posture index showed an exposure-effect relationship with the outcome. The job titles implied a large degree of exposure misclassification. ' ' CONCLUSIONS ': 'The posture index is recommended as a mechanical exposure index for analyses of interaction with other possible determinants of shoulder-neck pain (ie, psychosocial factors). The use of such an index instead of job titles in large population studies will reduce the risk of misclassification.
Keywords: exposure index; exposure response; internal consistency; job exposure; neck; pain; population study; predictive validity; questionnaire; reliability; shoulder